PENGARUH PELATIHAN INTERVAL TERHADAP DAYA TAHAN KARDIOVASKULAR DAN KECEPATAN - Sutisna, I Ketut (Universitas Pendidikan Ganesha, 2013)
This study aimed to determine the effect of interval training on cardiovascular endurance and speed in male student’s VII grade SMP N 2 Gerokgak school year 2012/2013. This type of research is experimental research with the modified design of the randomized pre-test post-test control group design. The study population was a student of male student’s VII grade SMP N 2 Gerokgak school year 2012/2013, 30 samples are determined by simple random sampling technique. The instrument used in this study for cardiovascular endurance is a multistage fitness test (MFT). While speed is a test instrument to sprint 50 meter were then analyzed with independent t-test at significance level (a) 0.05 with SPSS 16.0. Based on the analysis of research data using independent t-test showed cardiovascular endurance for the data obtained significance value count is smaller than the value of α (Sig < 0.05) is equal to 0.031. As for the speed data obtained significance value count is smaller than the value of α (Sig < 0.05) is equal to 0.003. From the results of the study concluded that: 1) interval training effect on increasing cardiovascular endurance in male student’s VII grade SMP N 2 Gerokgak school year 2012/2013, 2) interval training effect on increasing the speed in male student’s VII grade SMP N 2 Gerokgak school year 2012/2013.